IMPROVING STUDENTS’ NARRATIVE WRITING ACHIEVEMENT THROUGH READER’S THEATRE STRATEGY - Ririn Arsita; Machdalena Vianty; Soni Mirizon (The Journal of English Literacy Education: The Teaching and Learning of English as a Foreign Language, 2017)
Abstract: The objective of this study was to find out whether or not there were significant improvements in students’ narrative writing achievement and the aspects of  narrative writing between before and after the students were taught by using RT strategy. This study also investigated whether or not there was a significant difference in narrative writing achievement between the students who were taught by using RT strategy and those who were not. The sample of this study was 52 eleventh grade students of SMA Negeri 6 Prabumulih, South Sumatera. There were control and experimental groups. To collect the data, each group was assigned a pretest and a post test. The data were analyzed statistically by using paired sample and independent sample t-tests. The findings showed there were significant improvements in students’ narrative writing achievement and the aspects of narrative writing between before and after they were taught by using RT strategy. There was also a significant difference in narrative writing achievement between control and experimental groups. Therefore, it could be concluded that RT strategy can help improve eleventh graders’ narrative writing achievement. Keywords: narrative writing achievement, Reader’s Theatre strategy, eleventh graders